Foucault, Bakhtin, Ethnomethodology: Accounting for Hybridity in Talk-in-Interaction - Tate, Shirley Anne (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
Theorising hybridity within Postcolonial Studies is often done at a level which seems to exclude the everyday with the exception of its relevance for the cultural productions of migrants and dominant culture's "eating the other". This article uses the exploration of hybridity as an everyday interactional achievement within Black "mixed race" British women's conversations on identity to look at the production of an analytic method as process based on the task of the analyst as translator. This method as process thinks the links between FOUCAULT and BAKHTIN in the emergence of an ethnomethodologically inclined discourse analysis (eda) which is called on to make sense of a hybridity of the everyday where Black women reflexively translate discourses on identity positions in order to construct their own identifications in conversations. FOUCAULT's discourses and BAKHTIN's heteroglossia and addressivity allow us to theorise this movement in the talk which ethnomethodological transcription and theory enables us to first pinpoint occurring. The article begins by looking at first, how hybridity as identification emerges in talk-in-interaction through both speaker and analyst translations. Having established this, it then goes on to look at the theoretical convergences and divergences between FOUCAULT and BAKHTIN on the subject, identity and discourses in the eda enterprise. Looking at data through the lens of eda means that we must be aware of the subject positions which speakers identify as having the effect of constraining or facilitating particular actions and experiences and there is always the possibility for challenge to subjectificationURN: urn:nbn:de:0114-fqs0702107